Decompression without Fusion for Radiculopathy in the Setting of Degenerative Lumbar Scoliosis: A Meta-Analysis. (16th November 2020) - Echt, Murray; Schwarz, Julia; Hamad, Mousa; De la Garza Ramos, Rafael; Holland, Ryan; Fortunel, Adisson N; Cho, Samuel K; Yanamadala, Vijay; Yassari, Reza
Abstract: INTRODUCTION: Several expert opinions recommend that select patients undergo decompression alone for radicular symptoms in the setting of degenerative lumbar scoliosis (DLS) with stenosis as a preferred surgical option. However, to date there is no summary of the current available evidence to support this conclusion. METHODS: A PubMed/MEDLINE and Embase database search was performed for studies describing the outcomes of lumbar decompression without fusion in patients with DLS, defined as Cobb angle >10˚, and with 2-year minimum follow-up. Three outcomes were examined: 1) radiological Cobb angle progression, 2) reoperation rate including need for fusion, and 3) patient reported outcome measures and overall satisfaction. Weighted mean scores were calculated. RESULTS: Review of the literature yielded 11 studies (all level III-IV evidence). A total of 428 adult patients were included with average follow-up 3.5 years. Average age was 70.5. The average Cobb angle preoperatively, postoperatively, and change at final follow-up was 16.2˚, 17.7, and 1.47˚, respectively. Reoperation rate reported from all 11 studies was 9.7%. Nine of the studies specified the type of surgery; in total there was need for fusion in 15 cases and need for decompression in 14 cases. This represents a 5% rate of patients that required subsequent fusion and only 1.8% further decompression. Four studies reporting ODI found an average 21.6 point improvement. Overall patient satisfaction reported in 6 studies was 68.0%. There was little concurrence as to the risk factors for poor patient reported outcome, however some that were described were severe scoliosis (>25˚), mismatch of pelvic incidence-lumbar lordosis, positive sagittal imbalance after surgery (> 4.0cm), rotatory and lateral listhesis (>10%), and poor facet preservation. Interestingly, Cobb angle progression was not associated with worse outcome. CONCLUSION: For select patients with DLS, there is no increased rate of progression of Cobb angle compared with the natural history, low rate of subsequent fusion surgery, and favorable clinical outcomes. Predominantly radicular symptoms related to stenosis and mild scoliosis should be strongly considered for decompression without fusion.